PROFILING OF DEFORMITIES CAUSED BY THE LOSS OF MOLARS IN CHILDREN - Saidov A. A.; Aliev H. R. (Researchparks Publishing, 2022)
In most cases, as a result of early diagnosis and lack of treatment of dental anomalies in children, the occurrence of these defects and the prevention of complications is one of the most pressing problems of our time [2.4.6]. The age of the child at the time of premature removal of baby teeth, the timing of eruption of permanent teeth are essential for the formation of dentoalveolar deformities of varying severity; the number of missing teeth and the intensity of the carious process, as well as the functional group of destroyed or removed temporary teeth.